NOSTALGIA, NATIONALISM, AND THE US MILITIA MOVEMENT - Cooter, Amy ([S.l.] : ROUTLEDGE, 2024)
Nostalgia, Nationalism, and the US Militia Movement is an accessible primer on the contemporary US militia movement. Exploring the complicated history of militias in the United States, starting with the Revolutionary War period, this book leverages unique data from ethnographic fieldwork, in-depth interviews, and previously unseen archival materials from militia founder Norm Olson to detail the modern movement's origin and trajectory through the attempted insurrection of January 6th and beyond. This book uses the lenses of nostalgia and settler colonialism to explain militia members' actions and beliefs, including their understandings of both nationalism and masculinity. This approach situates militias ina broader political landscape and explains how and why they will continue to be relevant actors in American politics. A general audience will find this book approachable, and it will be of particular interest to people studying militias or other social movement organizations whose vision of an ideal nation rests on a nostalgic image of the past and potentially encourages political violence.
Keywords: Militia movements -- United States; SOCIAL SCIENCE / Violence in Society; POLITICAL SCIENCE / Political Ideologies / Conservatism & Liberalism